Three‐Dimensional Configuration of Induced Magnetic Fields Around Mars. Issue 8 (17th August 2022) - Zhang, Chi; Rong, Zhaojin; Klinger, Lucy; Nilsson, Hans; Shi, Zhen; He, Fei; Gao, Jiawei; Li, Xinzhou; Futaana, Yoshifumi; Ramstad, Robin; Wang, Xiaodong; Holmström, Mats; et al.
Abstract: Using over 6 years of magnetic field data (October 2014–December 2020) collected by the Mars Atmosphere and Volatile EvolutioN, we conduct a statistical study on the three‐dimensional average magnetic field structure around Mars. We find that this magnetic field structure conforms to the pattern typical of an induced magnetosphere, that is, the interplanetary magnetic field (IMF) which is carried by the solar wind and which drapes, piles up, slips around the planet, and eventually forms a tail in the wake. The draped field lines from both hemispheres along the direction of the solar wind electric field (E ) are directed toward the nightside magnetic equatorial plane, indicating that they are "sinking" toward the wake. These "sinking" field lines from the +E‐hemisphere (E pointing away from the plane) are more flared and dominant in the tail, while the field lines from the –E‐hemisphere (E pointing toward) are more stretched and "pinched" toward the plasma sheet. Such highly "pinched" field lines even form a loop over the pole of the –E‐hemisphere. The tail current sheet also shows an E‐asymmetry: the sheet is thicker with a stronger tailward J → × B → J× B force at +E‐flank, but much thinner and with a weaker J → × B → J× B (even turns sunward) at –E‐flank. Additionally, we find that IMF B x can induce a kink‐like field structure at the boundary layer; the field strength is globally enhanced and the field lines flare less during high dynamic pressure. Plain Language Summary: The dynamics and distribution of Martian space plasma are strongly coupled with the magnetic field structure. The knowledge of the magnetic field morphology of the Martian induced magnetosphere is essential to understanding the plasma dynamics of the Martian magnetosphere, for example, the ion escape. However, the real magnetic field morphology of the Martian magnetosphere remains unclear. To clarify the global magnetic field structure around Mars, we comprehensively study the three‐dimensional (3‐D) magnetic field structure of the Martian magnetosphere based on measurements from the Mars Atmosphere and Volatile EvolutioN spacecraft. We found that the reconstructed 3‐D magnetic field lines around Mars, governed by the orientation of upstream interplanetary magnetic fields (IMFs), are draped around the planet, and the morphology has an evident asymmetry along the direction of the solar wind electric field. We found the field structure is affected by the sunward component of the IMF, and the variations of solar wind dynamic pressure. We also quantitatively estimated the average structure of the tail current sheet and calculated the electromagnetic force exerted on the plasma in the current sheet, which is critical to interpreting the plasma escape through the tail current sheet. Key Points: The magnetic field structure has an evident hemispheric asymmetry along the direction of the solar wind electric field The tail current sheet is thicker and has a stronger tailward J → × B → J× B force near the flank of the +E‐hemisphere The effects of interplanetary magnetic field Bx, the dynamic pressure of solar wind on the field structure are surveyed respectively